A bed sheet is not as effective as a pelvic circumferential compression device in generating pelvic compression in patients with a suspected pelvic fracture. (April 2015) - Sinha, Shrestha; Ellicott, Helen; Gee, Ed; Steel, Alistair
Introduction: The Advanced Trauma Life Support protocol for emergent management of pelvic ring disruptions includes advising circumferential application of a bed sheet. A number of purpose-designed pelvic circumferential compression devices are commercially available. We assessed whether the Advanced Trauma Life Support-recommended simple bed sheet was able to generate the same pelvic pressure as provided by a pelvic circumferential compression device. Methods: A healthy volunteer was laid supine on an examination trolley and a pressure transducer was placed overlying the volunteer's greater trochanters. Two pelvic compression devices, a commercially available SAM Pelvic Sling II™ and a standard hospital bed sheet, were applied single handedly. The SAM Sling was applied according to the manufacturer's instructions and the bed sheet was applied in the way the participant felt best. The pressures generated at the level of the greater trochanters were measured at 2 min. The mean of the left and right pressures was recorded. Following removal of the first device, the second device was then placed and the pressures were again recorded at 2 min. Results: Twelve participants completed the study. The mean (standard deviation) pressure generated by the SAM sling was 107 (28.4) mmHg and by the bed sheet 54 (26.3) mmHg; the SAM sling generated significantly greater pressure ( p  < 0.0001). A variety of different methods for applying the bed sheet were observed. Conclusion: In patients with a suspected pelvic fracture, a bed sheet is unable to reliably generate pressures approaching those of a commercially available pelvic circumferential compression device.